(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Change has been the constant phenomena since time immemorial. It has political, economic and social dimensions whose convergence has created the history of human civilisation. This article offers a conceptual note on historiography. This article scatters some light on description of the relationship between “history and writing”, “history and politics”, and “history and society”. The aim is for a comprehensive understanding of the role of reading, writing, politics and society in historiography. In a particular manner, this article endeavored at explaining historiography with the attempt to establish correlation between historiography and social change. This article adopts analytical method. Doing so, it focuses on “how social change has impacted on historiography”. In this context, the article justifies that historiography is being affected and also affects social change.